Let presidents fail: Congressional deference to presidents as gambling on failure. (28th April 2022) - Kang, Myunghoon
Congress's power of the purse is effective enough to block the implementation of a policy Congress disagrees with, especially in the case of foreign policies initiated by presidents. However, it is puzzling that congressional deference to presidents, instead of defiance, has been common. Conventionally, presidents' informational advantages over Congress have been presented as the main account for congressional deference. This account connotes that congressional deference is Congress's surrender to presidents because Congress wants a successful outcome and presidents' policies are more likely to succeed. However, I present a model demonstrating that congressional deference occurs even if there is no such asymmetric information. The result is that the deference can be Congress's gambling on presidents' failure. Congress may defer to presidents not because Congress wants the success of presidents' policies but because Congress wants to show presidents' failure to convince voters that Congress's policy is better than those of presidents.